Embodiment, identity and disability sport : an ethnography of elite visually impaired athletes - Powis, Ben (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book investigates the complex relationship between embodiment, identity and disability sport, based on ethnographic research with an international-level visually impaired cricket team. Alongside issues of empowerment, classification and valorisation, it conceptualises the sensuous dimension of being in disability sport and challenges the idealised notion of the sporting body. It explores the players' lived experiences of participating and competing in an elite disabled sport culture, and uses an embodied theoretical approach drawing upon sociology, phenomenology and contemporary disability theory to examine aspects of this previously unexamined research 'site', both on and off the pitch. Written in a way that values and accurately represents the participants' traditionally marginalised voices, the book analyses the role that elite disability sport plays in the construction of identity and helps us to better understand the relationships between disability, sport and wider society. Embodiment, Identity and Disability Sport is essential reading for any student, researcher, practitioner or policy-maker working in disability sport, and a source of useful new perspectives for anybody with an interest in the sociology of sport or disability studies"--
An introduction to visually impaired cricket : the opening delivery -- Disability, sport and social theory -- The sensuous experiences of visually impaired cricket -- Elite disability sport and empowerment : from the playground to the oval -- Classification, valorisation and the hierarchy of sight -- Identity formation through elite disability sport -- Embodiment, identity and disability sport : the close of play.
OCLC-licensed vendor bibliographic record.
Keywords: Blind cricket players; Cricket for people with visual disabilities -- Social aspects; Group identity; Sociology of disability; SPORTS & RECREATION / General; SPORTS & RECREATION / Sociology of Sports